Simulation, synthesis, and analysis of strontium-doped ZnO nanostructures for optoelectronics and energy-harvesting devices - Anjum, Muhammad Shafiq; Ashraf, Muhammad Waseem; Tayyaba, Shahzadi; Imran, Muhammad (Frontiers in Materials, 2023)
The demand of clean and sustainable alternative energy resources is linearly increasing day by day due to prevailing electricity crisis. The small-scale energy harvesting are considered as a sustainable way to generate clean energy. Advanced energy solar cell mainly dye-sensitized solar cell use solar energy and convert it into electrical energy. Similarly, MEMS based piezoelectric materials are used to convert the mechanical energy into electrical energy. For these applications, Zinc Oxide (ZnO) is considered as one of the most suitable materials with high conductive, tunable band-gap and piezo-electric properties. However, altering of these properties can be carried out by the addition of metal and other materials. Several research work has been carried out to study the addition of conductive metal as a dopant to alter the properties of Zinc oxide. In this work the Strontium (Sr) has been doped in ZnO to form nanostructure for application in DSSC and MEMs energy harvesters. Analysis has been conducted using the simulation and fabrication method. The results show that the doping and the pore size of the substrate (Anodic Aluminum oxide membrane) largely affect the output voltage and current. The difference between the simulated and experimental results was less than 1%, which shows the accuracy of the simulation. Tuning of the band-gap can be observed by the addition of Sr in the ZnO nanostructure. For MEMs energy harvester, Sr doped ZnO nano-structures deposited on AAO shows 7.10 mV of voltage and 1.11 uA of current output. The addition of Sr doping in ZnO shows the improvement in the generated current and voltage for energy harvester and improvement in overall power conversion efficiency for dye sensitized solar cell. Microelectromechanical system (MEMS) based energy harvesting devices as well as low cost advanced solar cell are promising in order to improve the efficiency of the energy generation at small scale.